2015
DOI: 10.1021/acs.est.5b02112
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Enhances Bioavailability of Copper to Marine Phytoplankton

Abstract: Emiliania huxleyi, a ubiquitous marine algae, was cultured under replete and Cu-limiting conditions to investigate Cu uptake strategies involving thiols and associated redox reactions; comparisons to a model diatom, Thalassiosira pseudonana, were also drawn. Cu-limitation increased rates of cell surface reduction of Cu(II) to Cu(I) in E. huxleyi but not in T. pseudonana. Furthermore, Cu-limited E. huxleyi cells took up more Cu when cysteine was present compared to when no ligand was added, although a dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 50 publications
2
59
0
Order By: Relevance
“…Moreover, if FeL 2 is highly bioavailable to phytoplankton, as suggested for EPS (Hassler et al, 2011b(Hassler et al, , 2014, this pool could potentially benefit phytoplankton growth (e.g., Hassler et al, 2011b). In this case, weak ligands would be important for iron phytoplankton nutrition, as reported for other metals such as Zn (Aristilde et al, 2012) and Cu (Walsh et al, 2015).…”
Section: Implications Of the Co-existence Of Iron-binding Ligandsmentioning
confidence: 89%
“…Moreover, if FeL 2 is highly bioavailable to phytoplankton, as suggested for EPS (Hassler et al, 2011b(Hassler et al, , 2014, this pool could potentially benefit phytoplankton growth (e.g., Hassler et al, 2011b). In this case, weak ligands would be important for iron phytoplankton nutrition, as reported for other metals such as Zn (Aristilde et al, 2012) and Cu (Walsh et al, 2015).…”
Section: Implications Of the Co-existence Of Iron-binding Ligandsmentioning
confidence: 89%
“…Few studies describe the role of polyphosphate bodies in marine algae however the status of high density P bodies in the marine seaweed Macrocystis pyrifera have also been observed to alter with varying water quality characteristics. 49 Detailed investigations on cell morphology along with elemental analyses of the marine algae, Tetraselmis suecica, indicated that after Cu exposure, Cu was stored in P-rich bodies with characteristics similar to polyphosphate bodies. 50 Daniels and Chamberlain 45 also reported that Cu was associated with P, S and Ca bodies in the Cu-tolerant marine alga Amphora veneta (as was found in this study); however, they also observed that Cu was found in spherical bodies that were not rich in P. Polyphosphate bodies in microalgae clearly play a role in the detoxification of Cu in microalgae; however, whether this role is via direct binding of Cu to polyphosphates or other binding sites within polyphosphate granules, or other compartments rich in S and Ca, requires further investigation and is likely to be species specific.…”
Section: Discussionmentioning
confidence: 99%
“…Cu(II) is reduced to Cu(I) within 2-40 min by Cu(I) binding thiols like glutathione and cysteine (Leal and van den Berg, 1998). Cu-limitation has been demonstrated to increase rates of cell surface reduction of Cu(II) to Cu(I) in Emiliania huxleyi (Walsh et al, 2015). They demonstrated that cysteine can increase the bioavailability of copper to copper-limited cells through the reductive release of Cu(I) from Cu(II) ligands such as EDTA.…”
Section: Implications For Thaumarchaeotamentioning
confidence: 99%
“…The bloom starts when the free Cu ′ is already very low (Figure 5A), indicating that the availability of inorganic Cu ′ , whether as Cu(I) or as Cu(II), is not important. We hypothesize that the copper arrives at the cell as a Cu(I)-thiol species, where there is a direct exchange of copper to Cubinding groups on the cell wall, allowing active transport of the copper into the cell through a high affinity transporter, as described for E. huxleyi (Walsh et al, 2015). We suspect that the low Cu 2+ is not driven directly by the Thaumarchaeota through production of L 1 , but rather that L 1 is released independently, likely by other microorganisms in the water column or from the sediment and pore waters.…”
Section: Implications For Thaumarchaeotamentioning
confidence: 99%
See 1 more Smart Citation